Clinical and biochemical features of aromatic L-amino acid decarboxylase deficiency - Brun, L.; Ngu, L. H.; Keng, W. T.; Ch'ng, G. S.; Choy, Y. S.; Hwu, W. L.; Lee, W. T.; Willemsen, M. a. a. P.; Verbeek, M. M.; Wassenberg, T.; Régal, L.; Orcesi, S.; et al. (Neurology, 2010)
Objective: To describe the current treatment; clinical, biochemical, and molecular findings; and clinical follow-up of patients with aromatic l-amino acid decarboxylase (AADC) deficiency. - Method: Clinical and biochemical data of 78 patients with AADC deficiency were tabulated in a database of pediatric neurotransmitter disorders (JAKE). A total of 46 patients have been previously reported; 32 patients are described for the first time. - Results: In 96% of AADC-deficient patients, symptoms (hypotonia 95%, oculogyric crises 86%, and developmental retardation 63%) became clinically evident during infancy or childhood. Laboratory diagnosis is based on typical CSF markers (low homovanillic acid, 5-hydroxyindoleacidic acid, and 3-methoxy-4-hydroxyphenolglycole, and elevated 3-O-methyl-l-dopa, l-dopa, and 5-hydroxytryptophan), absent plasma AADC activity, or elevated urinary vanillactic acid. A total of 24 mutations in the DDC gene were detected in 49 patients (8 reported for the first time: p.L38P, p.Y79C, p.A110Q, p.G123R, p.I42fs, c.876G>A, p.R412W, p.I433fs) with IVS6+ 4A>T being the most common one (allele frequency 45%). - Conclusion: Based on clinical symptoms, CSF neurotransmitters profile is highly indicative for the diagnosis of aromatic l-amino acid decarboxylase deficiency. Treatment options are limited, in many cases not beneficial, and prognosis is uncertain. Only 15 patients with a relatively mild form clearly improved on a combined therapy with pyridoxine (B6)/pyridoxal phosphate, dopamine agonists, and monoamine oxidase B inhibitors.